2014
DOI: 10.1626/pps.17.194
|View full text |Cite
|
Sign up to set email alerts
|

Dual and Triple Intercropping: Potential Benefits for Annual Green Manure Production

Abstract: trial; pROL, partial relative land output value; ROL, ralative land output; S, sorghum sole cropping; SC, sorghum and crotalaria intercropping; SCH, sorghum, crotalaria, and sunflower intercropping; SH, sorghum and sunflower intercropping. Dual and Triple Intercropping: Potential Benefits for AnnualGreen Manure Production Kae Miyazawa, Masae Takeda, Toshifumi Murakami and Tohru Murayama (National Agricultural Research Center for Tohoku Region, Cover Crop Research Team, 50 Harajuku-minami, Fukushima 960-2156, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
0
5
0
2
Order By: Relevance
“…A tremendous increase in the world population within decades is a serious threat to agricultural sustainability that will lead to a reduction in cultivable land for food production (Tscharntke et al, 2012). Intercropping contributes significantly to the development of sustainable agriculture and the enhancement of food production (Miyazawa et al, 2014). The most beneficial legume and cereal intercropping system is soybean‐based maize–soybean intercropping due to its high yields, effective use of resources and minimum prevalence of weeds, diseases and attack from insect pests than in individual cropping systems (Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A tremendous increase in the world population within decades is a serious threat to agricultural sustainability that will lead to a reduction in cultivable land for food production (Tscharntke et al, 2012). Intercropping contributes significantly to the development of sustainable agriculture and the enhancement of food production (Miyazawa et al, 2014). The most beneficial legume and cereal intercropping system is soybean‐based maize–soybean intercropping due to its high yields, effective use of resources and minimum prevalence of weeds, diseases and attack from insect pests than in individual cropping systems (Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the results of the studies investigating this diversity-stability relationship are contrasted. Several studies revealed no clear advantage of increasing the number of species in terms of yield stability in mixtures of few species (up to 7 species) (Sanderson, 2010;Miyazawa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Sistem tanam tumpangsari memiliki beberapa keunggulan dibandingkan dengan monokultur (Lithourgidis et al 2011). Tumpangsari berperan penting dalam keberlanjutan pembangunan pertanian dan produksi pangan di seluruh dunia (Rodríguez-Navarro et al 2010;Miyazawa et al 2014), dan merupakan salah satu upaya intensifikasi pertanian untuk meningkatkan produksi pertanian pada kondisi ketersediaan lahan yang terbatas (Phala et al 2011). Tumpangsari juga dapat meningkatkan produksi per satuan luas melalui penggunaan sumber daya yang efektif, termasuk air, unsur hara, dan energi matahari (Nasri et al 2014), memberikan keuntungan yang lebih tinggi dibandingkan dengan monokultur dalam hal hasil dan efisiensi penggunaan lahan (Mao et al 2012).…”
Section: Pendahuluanunclassified